Comparison of homologous and heterologous prime-boost immunizations combining MVA-vectored and plant-derived VP2 as a strategy against IBDV - Richetta, Matias Daniel; Gomez, Evangelina Raquel; Lucero, Maria Soledad; Chimeno Zoth, Silvina Andrea; Gravisaco, María José; Calamante, Gabriela; Berinstein, Analia (2017)
Different immunogens such as subunit, DNA or live viral-vectored vaccines against Infectious Bursal Disease virus (IBDV) have been evaluated in the last years. However, the heterologous prime-boost approach using recombinant modified vaccinia Ankara virus (rMVA), which has shown promising results in both mammals and chickens, has not been tried against this pathogen yet. IBD is a highly contagious and immunosuppressive disease of poultry that affects mainly young chicks. It is caused by IBDV, a double-stranded RNA virus carrying its main antigenic epitopes on the capsid protein VP2. Our objective was to evaluate the immune response elicited by two heterologous prime-boost schemes combining an rMVA carrying the VP2 mature gene (rVP2) and a recombinant VP2 protein produced in Nicotiana benthamiana (pVP2), and to compare them with the performance of the homologous pVP2-pVP2 scheme usually used in our laboratory. The SPF chickens immunized with the three evaluated schemes elicited significantly higher anti-VP2 antibody titers (p < 0.001) and seroneutralizing titers (p < 0.05) and had less T-cell infiltration (p < 0.001), histological damage (p < 0.001) and IBDV particles (p < 0.001) in their bursae of Fabricius when compared with control groups. No significant differences were found between both heterologous schemes and the homologous one. However, the rVP2-pVP2 scheme showed significantly higher anti-VP2 antibody titers than pVP2-rVP2 and a similar tendency was found in the seroneutralization assay. Conversely, pVP2-rVP2 had the best performance when evaluated through bursal parameters despite having a less potent humoral immune response. These findings suggest that the order in which rVP2 and pVP2 are combined can influence the immune response obtained. Besides, the lack of a strong humoral immune response did not lessen the ability to protect from IBDV challenge. Therefore, further research is needed to evaluate the mechanisms by which these immunogens are working in order to define the combination that performs better against IBDV